Searching for new sources of innovative products for the food industry within halophyte aromatic plants: In vitro antioxidant activity and phenolic and mineral contents of infusions and decoctions of Crithmum maritimum L. - Pereira, Catarina Guerreiro (2019)
Aromatic halophyte plants are an outstanding source of bioactive compounds and natural products with potential use in the food industry. This work reports the in vitro antioxidant activity, toxicity, poly phenolic profile and mineral contents of infusions and decoctions from stems, leaves and flowers of Crithmum maritimum L, an aromatic and edible maritime halophyte (sea fennel). Aspalathus linearis (Burm.f.) Dahlg. (rooibos) herbal tea was used as a reference. Sea fennel's tisanes, particularly from leaves, were rich in phenolic compounds and five of them (p-hydroxybenzoic and ferulic acids, epicatechin, pyrocatechol and 4-hydroxybenzaldehyde) were here described in C maritimum for the first time. Chlorogenic acid was the dominant phenolic determined. Na was the most abundant mineral in all tisanes followed by Ca and Mg in leaves' tisanes and K in flowers. Sea fennel's samples had a similar antioxidant activity than those from A. linearis, and had no significant toxicity towards four different mammalian cell lines. Altogether, our results suggest that sea fennel can be a source of products and/or molecules for the food industry with antioxidant properties and minerals in the form, for example, of innovative health-promoting herbal beverages.